Trabecular Bone is Increased in a Rat Model of Polycystic Ovary Syndrome - Mujica, Lady Katerine Serrano; Glanzner, Werner Giehl; Prante, Amanda Luiza; Rissi, Vitor Braga; Correa, Gabrielle Rebeca Everling; Premaor, Melissa Orlandin; Antoniazzi, Alfredo Quites; Gonçalves, Paulo Bayard Dias; Comim, Fabio Vasconcellos (Experimental and Clinical Endocrinology & Diabetes, 2020)
Polycystic ovary syndrome (PCOS) in an intricate disorder characterized by reproductive and metabolic abnormalities that may affect bone quality and strength along with the lifespan. The present study analysed the impact of postnatal androgenization (of a single dose of testosterone propionate 1.25 mg subcutaneously at day 5 of life) on bone development and markers of bone metabolism in adult female Wistar rats. Compared with healthy controls, the results of measurements of micro-computed tomography (microCT) of the distal femur of androgenized rats indicated an increased cortical bone volume voxel bone volume to total volume (VOX BV/TV) and higher trabecular number (Tb.n) with reduced trabecular separation (Tb.sp). A large magnitude effect size was observed in the levels of circulating bone formation Procollagen I N-terminal propeptide (P1NP) at day 60 of life; reabsorption cross-linked C-telopeptide of type I collagen (CTX) markers were similar between the androgenized and control rats at days 60 and 110 of life. The analysis of gene expression in bone indicated elements for an increased bone mass such as the reduction of the Dickkopf-1 factor (Dkk1) a negative regulator of osteoblast differentiation (bone formation) and the reduction of Interleukin 1-b (Il1b), an activator of osteoclast differentiation (bone reabsorption). Results from this study highlight the possible role of the developmental programming on bone microarchitecture with reference to young women with PCOS.
Keywords: micro CT; developmental programming; animal models of PCOS; bone; androgens